Refractory hypoxia and saturation gap in a COVID-19 patient - Mobarak, Abidah; C. Thambiah, Subashini; Masiman, Ana Daliela; Samsudin, Intan Nureslyna; Lai, Yin Ye (Elsevier, 2024)
Acquired methemoglobinemia, predominantly due to oxidizing medications occurs when heme iron in hemoglobin is oxidized from ferrous to ferric ion and binds oxygen irreversibly leading to functional anemia, cyanosis, and tissue hypoxia. We report a case of a 60-year-old man with multiple comorbidities who was diagnosed with coronavirus disease 2019 (COVID-19) and developed methemoglobinemia after consumption of prescribed supplements. He presented with dyspnea and cyanosis. An oxygen saturation gap with characteristic chocolate-brown arterial blood indicated methemoglobinemia. Outsourced methemoglobin (MetHb) was increased at 9.0%. Despite aggressive intervention, he succumbed to his illness. In this case, we discuss the pathophysiology of why some individuals, especially the elderly with COVID-19 are more susceptible to develop methemoglobinemia after possibly being exposed to oxidizing agents. Laboratory methods for assessing oxygen saturation, including pulse oximetry, arterial blood gas and co-oximetry are examined in relation to this case. The importance of considering a diagnosis of methemoglobinemia based on clinical and biochemical findings although MetHb assay or co-oximetry are not readily available is also emphasized. © 2024 The Authors